Factors Influencing Atypical Clinical Presentations during the 2017 Madagascar Pneumonic Plague Outbreak: A Prospective Cohort Study - Salam, Alex P.; Raberahona, Mihaja; Andriantsalama, Prisca; Read, Liam; Andrianarintsiferantsoa, Faraniaina; Razafinambinintsoa, Tiana; Rakotomalala, Rado; Hasiniatsy, Rodrigue N. E.; Razafimandimby, Dominique; Castle, Lyndsey; Funk, Anna; Mangahasimbola, Reziky T.; et al. (The American journal of tropical medicine and hygiene, 2020)
In late 2017, Madagascar experienced a large urban outbreak of pneumonic plague, the largest outbreak to date this century. During the outbreak, there were widespread reports of plague patients presenting with atypical symptoms, such as prolonged duration of illness and upper respiratory tract symptoms. Reported mortality among plague cases was also substantially lower than that reported in the literature (25% versus 50% in treated patients). A prospective multicenter observational study was carried out to investigate potential reasons for these atypical presentations. Few subjects among our cohort had confirmed or probable plague, suggesting that, in part, there was overdiagnosis of plague cases by clinicians. However, 35% subjects reported using an antibiotic with anti-plague activity before hospital admission, whereas 55% had antibiotics with anti-plague activity detected in their serum at admission. Although there may have been overdiagnosis of plague by clinicians during the outbreak, the high frequency of community antibiotic may partly explain the relatively few culture-positive sputum samples during the outbreak. Community antibiotic use may have also altered the clinical presentation of plague patients. These issues make accurate detection of patients and the development of clinical case definitions and triage algorithms in urban pneumonic plague outbreaks difficult.